No Child Left Behind: Who Wins? Who Loses? - Arce, Josephine (Social justice, 2005)
Part of a special issue on challenging corporate control of schools and communities. The writers examine the effects of the No Child Left Behind Act of 2002, which focuses on policy and distribution of funds to public schools. They discuss the law in relation to corporate profit-making, its direct effect on a student population consisting of 4.4 million English Language Learners enrolled in U.S. public schools, and the increasing grassroots resistance by educators, teachers' unions, and parents. They state that the legislation's goals are very restrictive for lower-income families whose children attend low-income schools.